Effects of Gestation Pens Versus Stalls and Wet Versus Dry Feed on Air Contaminants in Swine Production - Peter C. Raynor; Shannon Engelman; Darby Murphy; Gurumurthy Ramachandran; Jeffrey B. Bender; Bruce H. Alexander (Journal of Agromedicine, 2018)

Evaluation of an electrostatic particle ionization technology for decreasing airborne pathogens in pigs - Carmen Alonso; Peter C. Raynor; Peter R. Davies; Robert B. Morrison; Montserrat Torremorell (Aerobiologia, 2016)

Weighing the Evidence of Common Beliefs in Obesity Research - Krista Casazza; Andrew Brown; Arne Astrup; Fredrik Bertz; Charles Baum; Michelle Bohan Brown; John Dawson; Nefertiti Durant; Gareth Dutton; David A. Fields; Kevin R. Fontaine; Steven Heymsfield; et al. (Critical Reviews in Food Science and Nutrition, 2015)

Major Conservation Policy Issues for Biodiversity in Oceania - R. T. KINGSFORD; J. E. M. WATSON; C. J. LUNDQUIST; O. VENTER; L. HUGHES; E. L. JOHNSTON; J. ATHERTON; M. GAWEL; D. A. KEITH; B. G. MACKEY; C. MORLEY; H. P. POSSINGHAM; et al. (Conservation Biology, 2009)
Oceania is a diverse region encompassing Australia, Melanesia, Micronesia, New Zealand, and Polynesia, and it contains six of the world's 39 hotspots of diversity. It has a poor record for extinctions, particularly for birds on islands and mammals. Major causes include habitat loss and degradation, invasive species, and overexploitation. We identified six major threatening processes (habitat loss and degradation, invasive species, climate change, overexploitation, pollution, and disease) based on a comprehensive review of the literature and for each developed a set of conservation policies. Many policies reflect the urgent need to deal with the effects of burgeoning human populations (expected to increase significantly in the region) on biodiversity. There is considerable difference in resources for conservation, including people and available scientific information, which are heavily biased toward more developed countries in Oceania. Most scientific publications analyzed for four threats (habitat loss, invasive species, overexploitation, and pollution) are from developed countries: 88.6% of Web of Science publications were from Australia (53.7%), New Zealand (24.3%), and Hawaiian Islands (10.5%). Many island states have limited resources or expertise. Even countries that do (e.g., Australia, New Zealand) have ongoing and emerging significant challenges, particularly with the interactive effects of climate change. Oceania will require the implementation of effective policies for conservation if the region's poor record on extinctions is not to continue .